Does public report card matter? A 10-year interrupted time series analysis on total knee replacement. (9th June 2019) - Chen, Tsung-Tai; Hsueh, Ya-Seng (Arthur); Liaw, Chen-Kun; Shih, Ling-Na; Huang, Li-Ying
Abstract: Background: There is a lack of evidence that shows whether a report card can improve health outcomes in terms of infection rates or unscheduled readmission by using rigorous methods to evaluate its impact. Methods: We used the National Health Insurance Administration's claims database from 1 January 2004 to 30 December 2013 and a time series analysis to evaluate the impact of the quality report card initiative on three negative outcomes of total knee replacement for each quarter of the year, including the rates of superficial infection of a knee replacement, deep infection of knee arthroplasty and unplanned readmissions for surgical site infection. Results: These negative outcomes (original scale) do not show significant decreases in terms of superficial infection (−0.05‰, −0.63 to 0.53‰, P = 0.87), deep infection (−0.003‰, −0.19 to 0.18‰, P = 0.97) and unscheduled readmission (0.02‰, −0.21 to 0.25‰, P = 0.88). Conclusion: The total knee replacement public report card initiative did not improve the rate of infection and unscheduled readmission for surgical site infection. This report card in Taiwan should involve physicians' participation in the design and be tailored to be suitable for reading by patients in order to further enhance the chance of improvement in these negative outcomes.